2019
DOI: 10.1038/s41587-019-0037-y
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omic measurements of heterogeneity in HeLa cells across laboratories

Abstract: Reproducibility in research can be compromised by both biological and technical variation, but most of the focus is on removing the latter. Here we investigate the effects of biological variation in HeLa cell lines using a systems-wide approach. We determine the degree of molecular and phenotypic variability across 14 stock HeLa samples from 13 international laboratories. We cultured cells in uniform conditions and profiled genome-wide copy numbers, mRNAs, proteins and protein turnover rates in each cell line.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
287
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 289 publications
(333 citation statements)
references
References 69 publications
21
287
1
Order By: Relevance
“…ITH in preclinical models affects experimental results and conclusions . Currently, PDX models are used extensively for drug testing and personalized medicine screening .…”
Section: Clinical Significancementioning
confidence: 99%
“…ITH in preclinical models affects experimental results and conclusions . Currently, PDX models are used extensively for drug testing and personalized medicine screening .…”
Section: Clinical Significancementioning
confidence: 99%
“…Furthermore, others and we have shown that the relationship between k loss and mRNA concentration is informative in understanding the protein turnover regulation between conditions (Schwanhausser et al , ; McShane et al , ; Liu et al , 2017a, ). By per‐gene relative analysis, we revealed that the protein degradation for subunits of heteromeric protein complexes was preferably regulated to buffer against the chromosomal aneuploidy impact due to trisomy 21 or high‐grade genomic instability between different HeLa cell strains (Liu et al , 2017a, ). However, to date, a detailed, systematic investigation of mRNA– k loss correlation has been still lacking.…”
Section: Introductionmentioning
confidence: 95%
“…For example, the protein‐specific degradation rates ( k loss as a proxy in steady state cells in this report, Materials and Methods) can now be quantified by “pulse labeling” with stable isotope‐labeled amino acids in cells, i.e., pulse SILAC (or pSILAC) technique (Pratt et al , ; Schwanhausser et al , , ; Eichelbaum & Krijgsveld, ; Jovanovic et al , ). At the absolute scale, previous pSILAC studies have repeatedly discovered that the protein turnover rate can be influenced by protein abundance, because higher abundant proteins normally tend to be less degraded (Claydon & Beynon, ; Liu et al , 2017a, ). Furthermore, others and we have shown that the relationship between k loss and mRNA concentration is informative in understanding the protein turnover regulation between conditions (Schwanhausser et al , ; McShane et al , ; Liu et al , 2017a, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations